The Effect of Microfinance in Increasing UMKM Productivity in Indonesia - Irfanullah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to investigate the effect of microfinance on the productivity of UMKM as an important factor in sustainable economic growth in Indonesia. This study uses multiple linear regression methods and finds that the variable loan amount, loan repayments, and microfinance financial performance have a significant effect on UMKM.